The Duties of Thai Citizens in the Constitution of the Kingdom of Thailand:: Legal Status and Legal Engagement - เดชรักษา กษมา; สมทรัพย์ ชุติพงศ์ (Ganesha Journal, 2018)
The duties of Thai citizens in the Constitution have been regulated for more than 85 years, since the Constitution of 2475 B.E. to the Constitution of 2560 B.E., like the constitutions of many other countries, the rights and responsibilities of Thai citizens are codified in these statutes. In theory, even though, the legal status of the provisions of the Constitution on the duties of the people or citizens or individuals is not legal binding to enforce compliance with the Constitution, the real power of the Thai Constitution as the highest law and the prototypical law is established. As a result, the government enacted secondary legislation that directly effect the individual. By the power of this legislation the individual is obliged to follow, otherwise, the person may be liable for criminal or civil liability. Therefore, the provisions relating to the duties of the people or of the citizen or individual as prescribed by the Constitution are impacted indirectly through the provisions of secondary legislation. Individuals are bound by the provisions of this secondary legislation directly. However, some provisions of the Constitution may have a direct effect on the individual, not in the form of a criminal or civil liability, but in form of lost or acquired rights, such as losing the right to vote in a future election by not registering to vote in the current election. In addition, the provisions of the Constitution on the duty of citizens, or citizens or individual also reflect the awareness of the duties of the citizens to Thai society as the significant foundation for the national spirit.